Human Cardiac-Mesenchymal Stem Cell-Like Cells, a Novel Cell Population with Therapeutic Potential - Oldershaw, Rachel (Stem Cells Dev, 2019)
Cardiac stem/progenitors are being used in the clinic to treat patients with a range of cardiac pathologies. However, improvements in heart function following treatment have been reported to be variable, with some showing no response. This discrepancy in response remains unresolved. Mesenchymal stem cells (MSCs) have been highlighted as a regenerative tool as these cells display both immunomodulatory and proregenerative activities. The purpose of this study was to derive a cardiac MSC population to provide an alternative/support to current therapies. We derived human cardiac-mesenchymal stem cell-like cells (CMSCLC), so named as they share some MSC characteristics. However, CMSCLC lack the MSC trilineage differentiation capacity, being capable of only rare adipogenic differentiation and demonstrating low/no osteogenic or chondrogenic potential, a phenotype that may have advantages following transplantation. Furthermore, CMSCLC expressed low levels of p16, high levels of MHCI, and low levels of MHCII. A lack of senescent cells would also be advantageous for cells to be used therapeutically, as would the ability to modulate the immune response. Crucially, CMSCLC display a transcriptional profile that includes genes associated with cardioprotective/cardiobeneficial effects. CMSCLC are also secretory and multipotent, giving rise to cardiomyocytes and endothelial cells. Our findings support CMSCLC as a novel cell population suitable for use for transplantation.